2012
DOI: 10.3109/00016357.2011.645060
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation ofCurcuma zedoaria(Christm.) Roscoe fluid extract used in oral hygiene products

Abstract: According to the results, the zedoary fluid extract presents low cytotoxicity and probably can be used in the oral hygiene products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Looking for antiproliferative drugs with less toxicity toward normal cells seems especially necessary. Previous studies demonstrated that Curcuma zedoaria , as an anticancer drug, has demonstrated to have less negative effects on normal cells, 8 10 showing that fibroblasts of human mucus lineage maintained stable cell viability from 0 hours to 7 days, when treated with Curcuma zedoaria extract. In the present study, we found that ZGS, bioactive substances extracted from Curcuma zedoaria, increased the viability rates of HUVECs and significantly reduced the suppression of HUVECs cycle at the G0/G1 phase in comparison with sirolimus.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Looking for antiproliferative drugs with less toxicity toward normal cells seems especially necessary. Previous studies demonstrated that Curcuma zedoaria , as an anticancer drug, has demonstrated to have less negative effects on normal cells, 8 10 showing that fibroblasts of human mucus lineage maintained stable cell viability from 0 hours to 7 days, when treated with Curcuma zedoaria extract. In the present study, we found that ZGS, bioactive substances extracted from Curcuma zedoaria, increased the viability rates of HUVECs and significantly reduced the suppression of HUVECs cycle at the G0/G1 phase in comparison with sirolimus.…”
Section: Discussionmentioning
confidence: 98%
“…Curcuma zedoaria , a Chinese medicinal herb, has been used to treat cancers for more than 100 years, including gastric cancer, 5 hepatoma, 6 and uterine cervical cancer, 7 while it has low toxicity on normal cells, such as human umbilical vein endothelial cells (HUVECs), 8 gastric epithelial cells, 9 and fibroblasts of human mucus lineage. 10 Moreover, Curcuma zedoaria has been demonstrated to prevent inflammation, 11,12 oxidant, 13 and hepatic injury activities. 14 Zedoary guaiane-type sesquiterpenoids (ZGS) are bioactive constituents of Curcuma zedoaria .…”
Section: Introductionmentioning
confidence: 99%
“…Many in vitro tests such as MTT, trypan blue exclusion test, micronucleus are used to determine cell viability. [27,28,41,42,43,44,45,46]. Flow cytometry analysis is frequently recommended in terms of providing more reliable, faster and more sensitive results than other methods in evaluating cell viability and cytotoxicity [47].…”
Section: Discussionmentioning
confidence: 99%
“…menunjukkan bahwa Curcuma zedoaria bersifat biokompatibel dan aman digunakan sebagai produk oral. 10 Aktivitas antimikroba dari ekstrak kunyit putih telah diteliti dan menunjukkan adanya efek terhadap bakteri Gram positif, Gram negatif, dan fungi dengan diameter zona hambat 7-15 mm. 11 11Aktivitas antibakteri kunyit putih juga diteliti oleh Shahriar yang menunjukkan bahwa ekstrak Curcuma zedoaria menunjukan aktivitas yang signifikan terhadap beberapa bakteri Gram negatif yang diuji seperti Escherichia coli, Shigella boydii, dan Salmonella typhi dengan diameter zona hambat yang paling besar pada bakteri E. coli, yaitu sebesar 18 mm.…”
Section: Fernandesunclassified